Pengaruh Kualitas dan Harga Beras Hitam terhadap Kepuasan Konsumen di PD Dharma Santhika Kabupaten Tabanan - NI PUTU AYU TRESNA SUARI; I KETUT SUAMBA; I DEWA GEDE AGUNG (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2021)
The Effect of Quality and Price of Black Rice on Consumer Satisfaction in PD. Dharma Santhika Tabanan District Black rice has become a food product that attracts consumers' attention. The nutritional content and its role for health are the main attraction. In addition to the great quality, the price of black rice that competes with similar products is also a concern of consumers. These two factors certainly affect customer satisfaction. This study raises the issue of the effect of the quality and price of black rice on the satisfaction of consumers who shop at PD. Dharma Santhika. The test method used to answer the research problem is multiple linear regression. The number of respondents who were collected was 60 people. The test results showed a regression coefficient of black rice quality of 0.547 and ttest of 7.243 with a probability of 0,000. This means that there is a significant positive effect of black rice quality on consumer satisfaction. Tests on the price of black rice produce a regression coefficient of 0.445 and ttest of 5.901 with a probability of 0.000. So it can be concluded that the price of black rice also has a positive and significant impact on consumer satisfaction. Suggestions that can be given to improve the quality of black rice are to increase supervision of the harvesting process, packaging and storage at the store. The creation of good prices also needs to be done by creating prices that are comparable to the quality of the products offered.